Pengujian Karakteristik Fisika Biogasoline Sebagai Bahan Bakar Alternatif Pengganti Bensin Murni - I Gede Wiratmaja (Department of Mechanical Engineering, University of Udayana, 2010)
Scarcity of fuel, especially gasoline has become a major issue in recent years, so that the search should be conducted ofalternative fuels, one of them is to use a mixture biogasoline of pure gasoline and alcohol with a specific ratio, it is due to biofuels(alcohol ) can not stand alone as a pure substitute for conventional fuels. For that here the author makes biogasoline a mixture ofgasoline and alcohol 95% in the 3 comparisons (90:10), (85:15), (80:20) for gasoline and alcohol. Further testing physicalcharacteristics, which include testing density, fuel viscosity, specific gravity, flash point, gas point, and calorific value todetermine eligibility level as a fuel substitute for gasoline.Test results obtained from physical characteristics with a ratio biogasoline gasoline - alcohol (90:10), was most likelyphysical characteristics of gasoline. And the whole mixture of gasoline and alcohol is in the range of tolerance characteristicproperties of gasoline. Be known so that the maximum tolerance alcohol content in gasoline, in order to fit for use in gasolineengines without any modification. And with the addition of biogasoline making alcohol content exceeds the tolerance on thegasoline into the engine must be modified, so that later can be seen further performance.